The future role of agriculture in multifunctional rural development: The case of Italy - Viaggi, Davide (Applied Studies in Agribusiness and Commerce, 2011)
This paper addresses the issue of the role of agriculture in multifunctional rural development in Italy. Italy is characterised by high heterogeneity in terms of territorial composition, rural areas and the role of agriculture. The paper reviews the main multifunctionality concerns in Italy, by discussing rural development issues and policies and addressing the role of agriculture in such a context. The further development of agriculture and related future issues are then discussed, both in terms of dominant themes and most relevant policy design issues.